NKCC1-mediated traumatic brain injury-induced brain edema and neuron death via Raf/MEK/MAPK cascade - Lu, Kwok-Tung; Cheng, Nai-Chi; Wu, Chang-Yen; Yang, Yi-Ling (Critical care medicine, 2008)
Brain edema is one of the characteristic features of patients with severe traumatic brain injury. The aim of this study was to examine the effects of Na+-K+-2Cl- co-transporter on traumatic brain injury-induced brain edema and neuron damage and to elucidate the relationship between Na+-K+-2Cl- co-transporter and mitogen-activated protein kinase (MAPK) cascade. Laboratory investigation. University research laboratory. Male Wistar rats weighing 350-400 g. Anesthetized animals were subjected to a weight-drop device (450-g weight, 1.8-m height) to induce traumatic brain injury. The expression of Na+-K+-2Cl- co-transporter and phosphorylation of MAPK cascade were determined by Western blot test. We also analyzed the degree of brain edema and neuronal damage in this study. We found that the messenger RNA and protein of Na+-K+-2Cl- co-transporter were up-regulated mainly in hippocampus neurons from 2 to 24 hrs after traumatic brain injury. After traumatic brain injury, animals displayed severe brain edema and neuron damage. The phosphorylation of extracellular signal-regulated kinase, MAPK kinase, and Raf also was significantly elevated after traumatic brain injury. Bumetanide (15.2 mg/kg), a specific Na+-K+-2Cl- co-transporter inhibitor, significantly attenuated the neuronal damage and brain edema after traumatic brain injury by decreasing the phosphorylation of Raf/MEK/ERK cascade proteins. The present study suggests that Na+-K+-2Cl- co-transporter plays an important role in TBI-induced brain edema and neuronal damage via activation of MAPK cascade.